Identification of the highest potential human health and environmental hazard in contaminated sediment near the point sources in the northwest Persian Gulf. Issue 4 (20th April 2020) - Cheraghi, Mitra; Riyahi Bakhtiari, Alireza; Memariani, Mahmoud; Mohammadi, Jahangard; Bonduà, Stefano
Abstract: The overall goal of this work was to determine the concentration levels and the potential ecological risks of 30 polycyclic aromatic hydrocarbons in the Persian Gulf sediments, Iran. The study also predicted the bioaccumulation of PAHs using the Monte Carlo simulation. For these goals, 68 surface sediment samples were collected from the Persian Gulf in January 2017. Then, the experiments were performed with Soxhlet system, chromatographic column and GC-MS instrument. According to the Canadian Sediment Quality Guidelines, 35.29% of sampling sites exhibited high potential adverse biological effects and 79.41% of samples have a low probability of toxicity. The mean bioaccumulated concentrations of carcinogenic PAHs in the Persian Gulf were predicted as 207.78 ± 262.23, 116.06 ± 146.47 and 69.26 ± 87.41 ng g –1 for mollusks, shrimps and crabs, respectively. The mean Toxic Equivalency and Mutagenic Equivalent Quotient for sediments was 702.06 ± 1012.37 and 500.37 ± 665.71 ng g −1, respectively. The 95th percentile carcinogenic and non-carcinogenic risks calculated for children and adults were lower than the threshold values of 10 −6 and 1.0, respectively, revealing no potential health risk. The highest potential risks for toxicity were observed at sampling sites close to the Nowruz oil field and Mahshahr petrochemical economic zone based on the highest TEQcarc and MEQcarc values in this area.